Diseño e implementación de un módulo didáctico para automatización de motores trifásicos mediante plc step s7 1200 en la Universidad Técnica de Cotopaxi, extensión La Maná, año 2015 - Cañar Aguirre, Diego Armando (2015)
This project aims to build a training module for automating of phase motors Step S7 1200 PLC, monitored by TIA PORTAL software for the Laboratory for Electromechanical. With the implementation of the training module the student of Electromechanics Engineering in will be able to make their lab’s practices to acquire an experimental knowledge about the functioning and operation of PLCs.